Anjing Menggonggong Muazin Berlalu: Toa Masjid, Gus Yaqut, dan Semiotika Morris - Safitri, Tika Sari; Atikurrahman, Moh. (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
Gus Yaqut's statement regarding Surat Edaran Nomor 5 Tahun 2022 tentang Pedoman Penggunaan Pengeras Suara di Masjid dan Musala garnered controversy. The reason is that the Minister of Religion of the Republic of Indonesia is considered to be comparing the call to prayer with the barking of dogs. The public reacted: the chairman of GP Ansor was accused of blasphemy against Islam. This study examines the statement of the Minister of Religion of the Republic of Indonesia using the Piercian semiotic approach. Using Morris's scheme of sign systems, this study examines verbal-linguistic facts that are considered fatal. The research method used is qualitative with a note-taking technique. The results of the data analysis are described descriptively. The research data in the form of syntagms were tested as semiotic facts, both grammatically and pragmatically meaningful. The results showed that from the three categories of Morris semiotics (syntax, semantics, and pragmatics) which were operationalized in the statement of the Minister of Religion of the Republic of Indonesia, there was no fact of blasphemy. The syntactic relation between “adhan” and “dog barking” is a grammatical construction as an analogy which in public rhetoric is used to express “audiotive noise” in society. The analogy is not a comparison (binary) to make an alignment but concretizes a statement so that the message is understood easily by the recipient of the message. The analogy is carried out so that the substance of the Circular Letter of the Minister of Religion of the Republic of Indonesia is accepted by the public. Meanwhile, the facts that have happened show that the opposite confirms that the language entity in the community is very dynamic, wild, and sometimes acrobatic from the initial goal.